2006
DOI: 10.1136/ip.2005.009399
|View full text |Cite
|
Sign up to set email alerts
|

Validating self reported home safety practices in a culturally diverse non-inner city population

Abstract: Use of safety devices and practices by parents of preschool aged children reported in a face to face interview are generally reliable. Reliability increases if the interview is conducted in the home. Parents may also be more willing to report potential problems if they perceive they may receive corrective assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Studies investigating the validity of parental report of home safety practices have found it to be generally reliable,23–25 particularly if interviews were carried out in the home23 or if exploring relative differences between groups rather than identifying individual need or risk 26. Mothers were asked about a limited number of safety equipment items (not, eg, window and cupboard locks which would also be relevant); additionally, it was not known whether the equipment was being used correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the validity of parental report of home safety practices have found it to be generally reliable,23–25 particularly if interviews were carried out in the home23 or if exploring relative differences between groups rather than identifying individual need or risk 26. Mothers were asked about a limited number of safety equipment items (not, eg, window and cupboard locks which would also be relevant); additionally, it was not known whether the equipment was being used correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Past research indicates that the reliability of parental response is highest when the parent perceives the response will result in assistance (Hatfield et al 2006). Further, comparisons of the rates of children at risk are generally consistent with other studies using more traditionally formatted assessments (Whiteside-Mansell et al 2007).…”
Section: Discussionmentioning
confidence: 66%
“…The reason for this discrepancy could likely be the setting of the initial interview, via telephone in advance of the home observation in the 2003 study as opposed to in the home at the time of home observation in the present study. The validity of respondent-reported home safety behaviours has been seen to decrease when questions are asked over telephone rather than in the home 7 8 10. Overall, self-report of SA coverage has shown troublingly low validity, and research that needs to rely on self-report to evaluate programmes or monitor trends should bear in mind the degree to which there is error in such measurement, especially with regard to which population groups may be at increased risk for incorrectly reporting their levels of protection.…”
Section: Discussionmentioning
confidence: 99%
“…One study in King County, Washington, found high positive predictive values (PPVs) for self-reports of most safety behaviours including a PPV of 89% for having SAs on every level of the home (the observation did not assess whether alarms were functioning) 6. Another study in a low-income area of Oklahoma found that although 66% of households reported having any working SAs, when tested, only 49% of households had them,7 while another study in Dane County, Wisconsin, found a 90% PPV using the same measure 8. Earlier research conducted by two of the present authors with low-income families in Baltimore found a low PPV of 52% for self-reports of having at least one working SA.…”
Section: Background and Introductionmentioning
confidence: 99%